Investigation of Mammal Arginase Inhibitory Properties of Natural Ubiquitous Polyphenols by Using an Optimized Colorimetric Microplate Assay - Bordage, Simon; Pham, Thanh-Nhat; Zedet, Andy; Gugglielmetti, Anne-Sophie; Nappey, Maude; Demougeot, Céline; Girard-Thernier, Corine (Planta Medica, 2017)
Polyphenols are plant secondary metabolites which possess many positive effects on human health. Although these beneficial effects could be mediated through an increase in nitric oxide synthase activity, little is known regarding the inhibitory effect of polyphenols on mammal arginase, an enzyme which competes with nitric oxide synthase for their common substrate, L-arginine. The aim of the present study was to determine the potential of a series of polyphenols as mammalian arginase inhibitors and to identify some structure-activity relationships. For this purpose, we first developed a simple and cost-effective in vitro colorimetric microplate method using commercially-available mammal bovine liver arginase (b-ARG 1). Among the ten tested polyphenolic compounds [chlorogenic acid, piceatannol, resveratrol, (−)-epicatechin, taxifolin, quercetin, fisetin, caffeic acid, quinic acid, and kaempferol], cholorogenic acid and piceatannol exhibited the highest inhibitory activities (IC50 = 10.6 and 12.1 µM, respectively) but were however less active as (S)-(2-Boronoethyl)-L-cysteine (IC50 = 3.3 µM), used as reference compound. Enzyme kinetic studies showed that both chlorogenic acid and piceatannol are competitive arginase inhibitors. Structural data identified the importance of the caffeoyl (3,4-dihydroxycinnamoyl)-part and of the catechol function in the inhibitory activity of the tested compounds. These results identified chlorogenic acid and piceatannol as two potential core structures for the design of new arginase inhibitors.
Keywords: phenolic compounds; arginase inhibitors; in vitro microplate assay